The play of nerves. Chopin in the era of mental disorder - Okulicz-Kozaryn, Radosław (Katedra Muzykologii, Wydawnictwo Naukowe PTPN, Wydawnictwo Naukowe UAM, 2010)
This article concerns the neurotic image of Chopin that took shape in the 1880s and became popular during the Young Poland period. At that time, features highlighted from earlier descriptions of the composer’s character – over-sensitivity, over-sentimentality, excessive delicacy, emotional instability and inner complexity – were most spectacularly portrayed in the works of painters and sculptors such as Władysław Podkowiński, Wojciech Weiss, Bolesław Biegas and the designer of the monument in the Łazienki Royal Baths Park in Warsaw – Wacław Szymanowski. Critics and writers also helped to form the new portrait of the composer: Stanisław Przybyszewski, Cezary Jellenta, Wacław Nałkowski and Antoni Potocki. Their utterances allow us to grasp the dependency of the new picture on the theory of neuroses, advanced in 1881 by George Miller Beard and then developed and popularised during the last quarter of the nineteenth century by Richard Kraff-Ebing and Paolo Mantegazza, among others. Nervousness was considered to be the dominated feature of modern civilisation. These concepts were also influential in music criticism. Representatives of nervousness in music proved to be the Richards – Wagner and Strauss – and also Juliusz Zarębski and Ignacy Jan Paderewski. The latter, in a speech from 1911, depicted Chopin implicitly in terms of nervousness, which was also becoming a feature of the Polish national character. However, theories of neuroses were applied first and foremost to the individual psyche. The fundamental inner conflict of modern man, exposed to a surfeit of external stimuli, supposedly arose between the over-developed brain and the rest of the nervous system, as the centre of feelings and will. And it was the paresis of emotions and volition that brought a growth in the role of music, which, depending on a particular author’s assessment, either was itself the result and expression of nervous disturbance and contributed to the further deepening of the process of destruction (the stance of Antoni Sygietyński) or else filled the space left by subordinated emotions and enabled them to rebuild (the opinion of the novelist Eliza Orzeszkowa). The view of Chopin as a eulogist of new sensitivity was made manifest in Maurice Rollinat’s volume of poetry Les Nervoses, which caused quite a stir in the mid 1880s, and it was represented in Poland by Zenon Przesmycki’s Życie, and a philosophical treatise by Jean-Marie Guyau published in that periodical in 1887.
Keywords: Young Poland; Fryderyk Chopin; modernism; nervousness; scientism; Theory of individual genius